2022
DOI: 10.4102/jef.v15i1.796
|View full text |Cite
|
Sign up to set email alerts
|

Impact of industrialisation on economic growth in Nigeria

Abstract: Orientation: The industrial sector contributes to the growth of other sectors of the economy. Despite the number of industries in various sectors of the economy, inclusive economic growth is still not met in Nigeria.Research purpose: This article examines the impact of industrialisation on the growth of Nigeria’s economy.Motivation for the study: There exists a divergence in the results of the existing empirical investigations conducted on Nigeria in comparison with other developing economies.Research approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 26 publications
(26 reference statements)
2
5
0
Order By: Relevance
“…This study supports the findings of Lugina et al (2022), who found that industrialization helps European and East Asian economies grow. The findings of this study are also consistent with previous studies that show that industrialization has a positive and significant relationship with economic growth (see Ibitoye et al, 2022;Yangailo & Chambani, 2023;Lugina et al, 2022;Bokosi, 2022;Wang & Su, 2019;Su & Yao, 2017). This finding contradicts previous research studies that found a negative relationship between industrialization and economic growth (Iheoma & Jelilov, 2017;Ibbih & Gaiya, 2013).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…This study supports the findings of Lugina et al (2022), who found that industrialization helps European and East Asian economies grow. The findings of this study are also consistent with previous studies that show that industrialization has a positive and significant relationship with economic growth (see Ibitoye et al, 2022;Yangailo & Chambani, 2023;Lugina et al, 2022;Bokosi, 2022;Wang & Su, 2019;Su & Yao, 2017). This finding contradicts previous research studies that found a negative relationship between industrialization and economic growth (Iheoma & Jelilov, 2017;Ibbih & Gaiya, 2013).…”
Section: Discussionsupporting
confidence: 86%
“…This is due to conflicting findings on the nature of the relationship that exists between economic growth and industrialization. Some studies have found that industrialization has a positive impact on economic growth (Yangailo & Chambani, 2023;Lugina et al,2022;Bokosi, 2022;Ibitoye et al,2022;Wang & Su, 2019;Su & Yao,2017), while others have not (Iheoma & Jelilov, 2017;Ibbih & Gaiya, 2013;Jelilov et al, 2016). This study was the first to be conducted in the Tongan context.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…On the other hand, there have been conflicting results regarding the nature of the association that exist between economic growth and industrialisation. Some studies have presented that industrialisation has a positive effect on economic growth (Ibitoye et al,2022;Lugina et al,2022;Su & Yao,2017;Wang & Su,2019). Whereas other research studies have not found any positive relations between industrialisation and economic growth (Ibbih & Gaiya,2013;Iheoma & Jelilov,2017;Jelilov et al, 2016).…”
Section: Article Infomentioning
confidence: 99%